Uptake and transfection efficiency of PEGylated cationic liposome–DNA complexes with and without RGD-tagging - Majzoub, Ramsey N. (2014)
Steric stabilization of cationic liposome–DNA (CL–DNA) complexes is required for in vivo applications such as gene therapy. PEGylation (PEG: poly(ethylene glycol)) of CL–DNA complexes by addition of PEG2000-lipids yields sterically stabilized nanoparticles but strongly reduces their gene delivery efficacy. PEGylation-induced weakening of the electrostatic binding of CL–DNA nanoparticles to cells (leading to reduced uptake) has been considered as a possible cause, but experimental results have been ambiguous. Using quantitative live-cell imaging in vitro, we have investigated cell attachment and uptake of PEGylated CL–DNA nanoparticles with and without a custom synthesized RGD-peptide grafted to the distal ends of PEG2000-lipids. The RGD-tagged nanoparticles exhibit strongly increased cellular attachment as well as uptake compared to nanoparticles without grafted peptide. Transfection efficiency of RGD-tagged PEGylated CL-DNA NPs increases by about an order of magnitude between NPs with low and high membrane charge density (σ(M); the average charge per unit area of the membrane; controlled by the molar ratio of cationic to neutral lipid), even though uptake of RGD-tagged particles is only slightly enhanced by high σ(M). This suggests that endosomal escape and subsequent transfection efficiency of RGD-tagged NPs is facilitated by high σ(M). We present a model describing the interactions between PEGylated CL–DNA nanoparticles and the anionic cell membrane which shows how the PEG grafting density and membrane charge density affect adhesion of nanoparticles to the cell surface.